Investigation of Non-cooldown SG Secondary Condition on the Natural Circulation Cooling Procedure - TATSUMI, Eisaku; SAKUMA, Wataru; MIYATA, Shinya; MARUYAMA, Manabu; OGAWA, Junto (Nuclear Science and Technology, 2017)
In typical pressurized water reactor (PWR), in case that one steam generator (SG) cannot be credited for the primary cooldown, it is necessary to homogenize primary coolant temperature among loops using at least one reactor coolant pump (RCP) for the plant cooldown. If the natural circulation condition is established due to unavailability of all the RCPs, the continuous cooldown using intact SGs causes to disturb the smooth depressurization because it leads to void generation in the top of the non-cooldown SG tube where the high temperature coolant is remained. For this purpose, W.Sakuma, et al.[1] suggested the outline of asymmetric cooldown procedure without any RCPs restart. Since the suggested procedure is based on only one secondary condition (SG dry-out) of non-cooldown SG, and hence the impact of difference of the secondary condition should be investigated. In this paper, the sensitivity analyses were performed to confirm the impact on the asymmetric cooldown procedure, and consequently, it was confirmed that the coolable range used in the procedure was expanded if the water inventory exists in non-cooldown SG. Therefore it was concluded that the coolable range which was defined with the SG dry-out condition in non-cooldown SG can be conservatively applied for the operating procedure.